Social representations of sexual and reproductive rights: experiences of young men deprived of freedom - Angélica Orozco-Idárraga; Angela García-Navarro; Jennifer Castillo-Bolaños; Helena Morales-Ortega; Yomaira García-Acuña (Universidade de São Paulo, 2021)
Abstract This paper aims to submit a research results whose objective is to interpret social representations considered by young inmate males from the Centro de Educaciòn El Oasis, in relation with sexual an reproductive rights and their incidence in adolescent pregnancy, in order to lead them to a resignification process evident in their own life project. It is a qualitative study developed from a participatory methodology in Colombia, 2015. The sample consisted of a total of 60 young adults, including 46 teens and managers. The techniques used were a social survey given to 46 adolescents, an unstructured interview to 30, focus groups and resignification workshops. The representations by teenagers and young people about the subject came from female figures, inculcated early, when still in their homes, according to the socio-cultural contexts in which they were inserted. Thus, their beliefs do not favor the development of practices aimed at preventing diseases and teenage pregnancy, in addition to reinforcing stereotyped ideals of masculinity and femininity and prejudices in relation to sex, prioritizing sexist and homophobic notions regarding gender roles.